Hukum Dalam Tantangan Perlindungan Penyandang Disabilitas Terhadap Kekerasan Seksual - Iqbal, Muhamad; Indriani, Iin (Pamulang Law Review, 2024)
Gender-based violence is defined as any action that results in physical harm or emotional distress, including threats of harm with certain behaviors, coercion to engage in harmful behaviors, and various forms of freedom-limiting oppression.One of the most pervasive and harmful forms of HAM violation is sexual violence, which includes both overt acts of violence and those that are more covert in nature, such as those caused by cultural and societal biases against the victims. Research in the field of law is research that employs specific methodologies, frameworks, and philosophies in order to analyze a particular legal phenomenon. The key topics of this investigation are intellectual property rights and commercial secrecy. The primary laws used in this study are the Manufacturing Act of 1999. This study makes use of qualitative data analysis. To be conceited in the Ucapan Jurisprudence: Any action taken with the intention of causing another person to behave in a way that is inconsistent with their own personal values is known as ancaman or ancaman. Lack of Integrity in Concrete Work Product Expression (Memaksa and Memperkosa): To "memaksa" someone is to order them to do something, demand it of them forcefully, or coerce them into taking action without their consent. In terms of legal protection, sexual abusers who target people with disabilities should face harsher penalties than those who target those without disabilities. People with disabilities have the same rights and responsibilities as everyone else. They need special housing and protection so they don't feel stigmatized for their deficiencies. According to Article 27(1) of our Constitution, "All citizens of a country are equal before the law and the government and must obey those laws and that government without exception.".